GEOLOGICAL CONTROLS ON INTACT ROCK STRENGTH. THE EFFECT OF ANISOTROPY - Σαρόγλου, χ.; Μαρίνος, Π.; Τσιαμπάος, Γ. (Bulletin of the Geological Society of Greece, 2004)
The factors that influence the strength and deformation of the intact rock are the mineral composition, the fabric, the grain size and the degree of alteration and weathering. Anisotropy is a characteristic of intact foliated metamorphic rocks (slates, gneisses, phyllites, schists). The current paper deals with the pronounced effect of the fabric of anisotropic rocks on the strength and deformation characteristics of intact rocks. It is part of ongoing research in the Department of Geotechnical Engineering, National Technical University of Athens. Testing was used to establish the anisotropic behaviour of selected metamorphic rocks. The effect of anisotropy on various mechanical properties (strength, deformation) and dynamic properties (wave velocity) was examined. The degree of strength anisotropy of these rocks can be indirectly estimated, by wave propagation through the rock, and thus they can be classified by means of geological and geotechnical indexes.